Tax Avoidance in Relationship on Capital Intensity, Growth Opportunities, Financial Distress and Accounting Conservatism - Yahya, Adibah; Asiah, Neng; Nurjanah, Rina (Journal of Business Management and Economic Development, 2023)
Tax avoidance is an act of legal tax avoidance, but in this case the state suffers losses from this action. There are several factors that affect tax avoidance including capital intensity, growth opportunities, financial distress, and accounting conservatism. This type of research uses quantitative research with company objects that are members of the Jakarta Islamic Index 70. Data sources use secondary data listed in the company's financial reports for the 2018-2021 period. A total of 105 research data were tested using the SPSS version 25 application. The test results showed that only capital intensity had a negative and significant effect on tax avoidance, while other variables had no effect on tax avoidance. The test results show that tax avoidance tends to be influenced by factors that affect cost reduction.